ダイ39ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1998 - 岸, 隆幸; キシ, タカユキ; 安田, 毅彦; ヤスダ, タケヒコ; 吹田, 俊明; フキタ, トシアキ; 堀川, 和久; ホリカワ, カズヒサ; 大河原, 望; オオカワラ, ノゾム; Kishi, Takayuki; Yasuda, Takehiko; et al. (2002)
P(論文) この報告は, 第39次南極地域観測隊気象部門が1998年2月1日から1999年1月31日まで昭和基地において行った気象観測の結果をまとめたものである。観測方法・測器・統計計算等は第38次観測隊とほぼ同様である。越冬期間中特記される気象現象としては次のものが挙げられる。1) 年間をとおして気象現象の変化が激しく, 年前半の気温は高めに経過した。3月の月平均気温は1位の高温を記録した。2) 6月3日から5日にかけてブリザードが昭和基地を襲来し, 最大風速46.4m/s, 最大瞬間風速54.8m/s(ともに6月の歴代1位)を記録した。9月は悪天が継続し, ブリザード日数は17日間を記録した。3) 10年連続で大規模なオゾンホールを観測し, 1998年9月, 11月, 12月及び1999年1月の月平均オゾン全量はその月として過去最低を記録した。オゾンホールの目安である220m atm-cmを下回る値が, これまでで最も遅い12月中旬まで観測された。 This paper describes the results of meteorological observations at Syowa Station from February 1,1998 to January 31,1999,carried out by the Meteorological Observation Team of the 39th Japanese Antarctic Research Expedition (JARE-39). The method of observation, instruments and statistical methods used by JARE-39 were almost the same as those used by the JARE-38 observation team. Remarkable weather phenomena observed during the period of JARE-39 were the following : 1) Changes in the weather were severe through out the year, and the surface temperature in the first half of the year was higher than average. The monthly mean temperature in March was the highest temperature on record. 2) A heavy snowstorm (blizzard) hit Syowa Station from June 3rd to 5th and recorded a maximum wind speed of 46.4m/s, with a peak gust of 54.8m/s (both the record high of June). Rough weather continued in September, and the number of blizzard days reached 17 days. 3) The large scale Antarctic ozone hole was observed for the tenth successive year, and the monthly mean total ozone amounts in September, November, December 1998 and January 1999 were recorded as the lowest in observation history for the respective months. The total ozone amount was less than 220m atm-cm indicating that the ozone hole, was observed until the middle of December, which was the latest in observation history. departmental bulletin paper